Cost and clinical effectiveness of aggressive surgical debridement and delayed primary closure of infected cardiac surgical wounds - Yousafzai, Sajjad Mohammad; Uğurlucan, Murat; Awan, Abid; Canver, Charles C. (NLM (Medline), 2022)
OBJECTIVE: Postoperative wound infection in cardiac surgery remains a subject of significant concern due to associated morbidity, prolonged hospital stay and rise in treatment cost. A conservative management approach to postoperative wound infection with topical dressings and healing by secondary intention is not cost-effective and cosmetic results are less acceptable. We developed our institutional protocol for the treatment of infected postoperative cardiac surgical wounds to reduce hospital stay and improve cosmetic outcome. This study aims to compare our institutional protocol with the conservative management approach. METHODS: Adult patients with postoperative superficial or deep sternal and/or leg wound infection were divided into two equal-sized groups and data collected from medical records. Group A was treated according to our institutional protocol of aggressive surgical debridement and delayed primary closure. Group B was treated according to conservative management with topical antiseptic wound dressings and healing by secondary intention. Data were analysed in retrospect with comparative statistics. RESULTS: A total of 30 patients took part in the study. Group A (n=15, seven male, eight female) had a mean age of 55.34±12.84 years. Group B (n=15, eight male, seven female) had a mean age of 56.46±10.21 years. Mean length of hospital stay in Group A and Group B was 5.13±2.06 and 36.67±22.28 days, respectively (p<0.0001). Calculated mean hospital costs were 16,271.61±6815.50 Saudi Riyals (approximately equivalent to $4330±700 USD) in Group A and 116,212.2±26,311 Saudi Riyals (approximately equivalent to $30,932±1813 USD) in Group B (p<0.05). Patients in Group A had linear scars comparable with primary postoperative wound scars, whereas patients in Group B had excessive non-linear scarring. CONCLUSION: In this study, cost and clinical effectiveness of aggressive surgical debridement and delayed primary closure was superior to conservative management with topical antiseptic wound dressings and healing by secondary intention in terms of a shorter hospital stay and better cosmetic outcome.
Keywords: Aggressive Surgical Debridement; Cardiac Surgical Wounds; Conservative Management; Debridement; Delayed Primary Closure; Infection; Wound; Wound Care; Wound Healing